PENDIDIKAN MULTIKULTURAL BAGI MAHASISWA DI PERGURUAN TINGGI HINDU MENUJU SIKAP MODERASI BERAGAMA - Wulandari, Ida Ayu Gde (JAPAM (Jurnal Pendidikan Agama), 2024)
Universities has an important role in shaping the character of the younger generation in developing and guiding them towards a better direction, especially Hindu universitie which is role models for other universities. It is hoped that multicultural education for students at Hindu Universities will lead to an attitude of religious moderation. Multicultural education can be developed in universities, especially Hindu universities so that the teachings of sarve sukhinah bhavantu can be understood comprehensively by Hindus. The development of multicultural education in higher education for students can be done through education, research and community service. Apart from that, multicultural education can also be carried out through supporting activities. Multicultural education in universities must be able to create a multicultural climate that can be taught through strategies that can accommodate diversity so that later universities can become multicultural laboratories which will lead to an attitude of religious moderation. This will also have an influence on the attitudes of Hindu students who have an understanding of multicultural education so that later they can provide solutions to multicultural problems that exist in the surrounding environment.